2022
DOI: 10.3390/soc12040103
|View full text |Cite
|
Sign up to set email alerts
|

Childcare Issues and the Pandemic: Working Women’s Experiences in the Face of COVID-19

Abstract: Purpose: The COVID-19 pandemic has drastically impacted everyday life. Not only has it assailed the world’s populations with millions of deaths and cases, but COVID-19 has also ravaged global economies and affected the lives of women and their children. The purpose of this study was to detail women’s experiences during the COVID-19 pandemic and the solutions they came up with to deal with the problems they encountered. Method: Data collection occurred in the midwestern United States, in the State of Indiana, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…According to the mothers in our sample, however, the most valued form of support for their wellbeing was the (partial and then full) return of childcare (Obeng et al, 2022 ):…”
Section: Discussionmentioning
confidence: 99%
“…According to the mothers in our sample, however, the most valued form of support for their wellbeing was the (partial and then full) return of childcare (Obeng et al, 2022 ):…”
Section: Discussionmentioning
confidence: 99%
“…However, as in other studies [ 32 , 40 ], it has been observed that difficulties related to time management are experienced more by female academic staff. Increased childcare burden and spending more time on cooking combined with work responsibilities [ 41 ] created more pressure on time management. Health was also mentioned as another disadvantage created by online teaching.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study findings, children experienced prevailing negative emotions during the pandemic, including anger, fear, and worry, particularly regarding the health of their loved ones. Boredom, loneliness, irritability, anxiety, and restlessness were also observed during the lockdown, leading to increased externalizing behaviors [ 37 , 38 ]. However, amidst these negative aspects, the lockdown period presented some positives.…”
Section: Discussionmentioning
confidence: 99%